Autonomous ribosome biogenesis in vitro - Yuishin Kosaka; Yumi Miyawaki; Megumi Mori; Shunsuke Aburaya; Chisato Nishizawa; Takeshi Chujo; Tatsuya Niwa; Takumi Miyazaki; Takashi Sugita; Mao Fukuyama; Hideki Taguchi; Kazuhito Tomizawa; et al. (Nature Communications)
Abstract Ribosome biogenesis is pivotal in the self-replication of life. In Escherichia coli, three ribosomal RNAs and 54 ribosomal proteins are synthesized and subjected to cooperative hierarchical assembly facilitated by numerous accessory factors. Realizing ribosome biogenesis in vitro is a critical milestone for understanding the self-replication of life and creating artificial cells. Despite its importance, this goal has not yet been achieved owing to its complexity. In this study, we report the successful realization of ribosome biogenesis in vitro. Specifically, we developed a highly specific and sensitive reporter assay for the detection of nascent ribosomes. The reporter assay allowed for combinatorial and iterative exploration of reaction conditions for ribosome biogenesis, leading to the simultaneous, autonomous synthesis of both small and large subunits of ribosomes in vitro through transcription, translation, processing, and assembly in a single reaction space. Our achievement represents a crucial advancement toward revealing the fundamental principles underlying the self-replication of life and creating artificial cells.